Peran Orang Tua Dalam Mengatasi Kenakalan Remaja Di Desa Kalumbatan Kabupaten Banggai Kepulauan - Parli, Gita Savitri Hi; Abdullah, Nuraeni; Azhar, Muh; Akil, Muhammad; Syahid, Akhmad (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to examine the role of parents in overcoming juvenile delinquency in Kalumbatan Village, Banggai Islands Regency. Qualitative research methods with a descriptive approach were used. Data were collected through intensive interviews with parents of teenagers and community leaders. The results of the study describe several forms of juvenile delinquency behavior in Kalumbatan Village, including smoking, drinking alcohol, theft, promiscuity, and fighting between groups. The role of parents in overcoming this behavior is identified in five main aspects: teaching moral and religious values, habituating positive behavior, providing motivation and support, developing roles as role models, and enforcing consistent family rules. This study highlights the importance of the active role of parents in preventing and overcoming juvenile delinquency behavior. A holistic approach that integrates teaching, habituation, motivation, role modeling, and enforcing family discipline has proven to be very important in forming positive adolescent characters and preventing deviant behavior.